An Audit of Changes in Outcomes of Acute Pain Service: Evolution Over the Last 2 Decades. Issue 40 (October 2015) - Low, Sheng Jia; Wong, Stanley Sau Ching; Qiu, Qiu; Lee, Yvonne; Chan, Timmy Chi Wing; Irwin, Michael G.; Cheung, Chi Wai
Abstract : Abstract: Acute pain services (APS) have evolved over time. Strategies nowadays emphasize multimodal analgesic regimes using a combination of nonopioid adjuvant analgesic drugs, peripheral nerve blocks, and local anaesthetic wound infiltration where appropriate. APS should be assessed over time to evaluate changes in outcomes which form the basis for future development. In this audit, data of patients under APS care in Queen Mary hospital, Hong Kong, between 2009 and 2012 were analyzed and compared with data from a previous audit between 1992 and 1995. The use of patient-controlled analgesia (PCA) was increased (from 69.3% to 86.5%, P < 0.001), while the use of epidural analgesia reduced (from 25.3% to 8.3%, P < 0.001) significantly. Although postoperative pain scores did not improve, PCA opioid consumption and the incidence of analgesia-related side effects were significantly less (all P < 0.001). More patients graded their postoperative analgesic techniques used as good when the results from these 2 audit periods were compared ( P < 0.001 and P = 0.001 for PCA and epidural analgesia, respectively). In conclusion, there has been a change in analgesic management techniques, but there has been no improvement in overall pain relief. While changes over time have led to improvement in important parameters such as the incidence of side effects and patient satisfaction, further and continuous efforts and improvements are warrant to reduce acute pain relief and suffering of the patients after the surgery.